2019
DOI: 10.1371/journal.pone.0214552
|View full text |Cite
|
Sign up to set email alerts
|

Transcription is a major driving force for plastid genome instability in Arabidopsis

Abstract: Though it is an essential process, transcription can be a source of genomic instability. For instance, it may generate RNA:DNA hybrids as the nascent transcript hybridizes with the complementary DNA template. These hybrids, called R-loops, act as a major cause of replication fork stalling and DNA breaks. In this study, we show that lowering transcription and R-loop levels in plastids of Arabidopsis thaliana reduces DNA rearrangements and mitigates plastid genome instability phenotypes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 100 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…Recent research showed WHIRLY mediated PEP-dependent transcription affected organelle genome stability. 30 , 31 , 44 WHY2 protein in potato and WHY1 and WHY3 proteins in Arabidopsis are also involved in maintaining low mutation rates and structural integrity of mitochondrial and chloroplast genomes. 27 , 28 , 29 , 45 The crystal structure of Solanum tuberosum WHY2, a close homolog of Arabidopsis WHY2, revealed that WHIRLY proteins bind to single-strand DNA to promote accurate repair of DNA double-strand breaks over an error-prone repair pathway 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research showed WHIRLY mediated PEP-dependent transcription affected organelle genome stability. 30 , 31 , 44 WHY2 protein in potato and WHY1 and WHY3 proteins in Arabidopsis are also involved in maintaining low mutation rates and structural integrity of mitochondrial and chloroplast genomes. 27 , 28 , 29 , 45 The crystal structure of Solanum tuberosum WHY2, a close homolog of Arabidopsis WHY2, revealed that WHIRLY proteins bind to single-strand DNA to promote accurate repair of DNA double-strand breaks over an error-prone repair pathway 29 .…”
Section: Resultsmentioning
confidence: 99%
“…WHY1/WHY3 proteins suppress error-prone microhomology-mediated recombination (MHMR) via nonspecific binding to single-stranded DNA (ssDNA) and inhibit high levels of ptDNA rearrangements. 27 , 28 , 29 , 30 , 31 WHY1 and WHY3 also dynamically balance ROS, and loss of their functions causes the development of white/yellow variegated leaves in about 5% of the plant population as well as other signs of stress and senescence. 32 , 33 , 34 WHY2 is another member of the WHY family; a similar effect is observed in potato when the why2 mutant is treated with DSB-inducer ciprofloxacin (CIP).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of the group of Normand Brisson, the double mutant why1tilwhy3 was combined with the sig6 mutant deficient in SIGMA 6 (SIG6), that is, a significant nucleus-encoded transcription factor for PEP ( Di Giorgio et al, 2019 ). By characterization of the triple mutant and pharmacological treatments with the transcription inhibitor rifampicin, the authors identified transcription as a major source of ptDNA instability.…”
Section: Impact Of Whirlies On Organelle Dna-associated Activitiesmentioning
confidence: 99%
“…In the A. thaliana mtDNA, we see slightly elevated XR-seq coverage of the CDS compared to the intergenic regions of the genome, but rRNA and tRNA genes, which are typically expressed more highly than CDS regions (82,83), have XR-seq coverage below or near the level of intergenic sequence (Figure S18, top left panel). This suggests that increases in expression may not correlate with increased levels of of incisions or repair activity as is observed in the A. thaliana nucDNA due to TC-NER (53).…”
Section: Variation In the Distribution Of Xr-seq Reads Among Genomic ...mentioning
confidence: 99%